The Relationship Between Screen Time and Nutritional Status of Children at SDN 060838 Medan in 2024 - Siregar, Anggi Dolse Maria; Yasirah, Tarisya; Dalimunthe, Siti Aisyah; Wijaya, Johanna Fransiska (Universitas Teuku Umar, 2024)
Excess weight in children and adolescents is a global health problem that can result in various serious complications. One of the main factors that trigger obesity is lack of physical activity, which is largely influenced by the length of time using screen devices. Screen use of more than two hours a day has been linked to increased sedentary behavior, decreased physical activity, disrupted sleep patterns, and unhealthy eating patterns, all of which contribute significantly to the risk of obesity. This study aims to assess the relationship between duration of screen use and nutritional status among students at SDN 060838 in Medan City. With a cross-sectional analytical research design, the sample used was 50 students selected from a population of 198 students. Data were analyzed using the Mann-Whitney test, which showed a statistically significant relationship between screen time duration and nutritional status (p < 0.001). These results emphasize the importance of managing screen time as a key element in preventing obesity in children. Appropriate policies and guidelines are needed to support their health and well-being, especially amidst the increasing use of screen devices for social and educational needs.